Stem cells and bone tissue - Rajendram, Rajkumar; Preedy, Victor R.; Patel, Vinood B. (CRC Press, 2013)
Preface Bone diseases, characterised by either fractures, stunting, loss of mineral composition or strength, are important causes of morbidity and mortality. For example worldwide there are 9 million new cases of fractures due to osteoporosis annually and this has increased by 50% in the past 2 decades. As the population ages, these fi gures will further increase, imposing burdens on individuals, communities, and health providers. As a result, new treatments and strategies are continually being developed to prevent bone diseases occurring and also to treat such conditions. Stem cells potentially offer a novel therapeutic platform to treat bone disease. They also help the scientist understand the molecular and cellular aetiology of bone disorders. Gaining knowledge on the nature and application of stem cell sciences is a prerequisite for understanding their potential in treating or preventing bone disorders. However, obtaining information on stem cells per se and their usage and applications in treating skeletal disorders is currently problematic, as such text-based material is either sporadic or directed towards the expert. This book Stem Cells and Bone Tissue is designed to address such limitations. It is multidisciplinary and covers all scientifi c levels. Stem Cells and Bone Tissue has three major sections: Section 1: Introductory Text and Sources of Stem Cells for Skeletal Tissue Section 2: Cellular and Molecular Aspects Section 3: Conditions, Applications, Treatments and Repairs The simplistic nature of the main section headings, however, should not detract from the fact that individual chapters are highly detailed. Coverage includes for example, general aspects of stems cells, sources of stems cells, isolation and purifi cation, applications in.